Vaping – A Beneficial Alternative to Traditional Cigarettes or an Unexplored Danger? - Błasiak, Paulina; Ślusarska, Aleksandra; Mikołajec, Patryk; Bilecka, Barbara; Mędyk, Jolanta; Wirkijowska, Małgorzata; Wirkijowski, Jakub; Patarocha, Yauheniya; Rogulski, Michał; Huk, Ruslan (Quality in Sport, 2025)
The aim of this study is to assess the risks associated with e-cigarette use, particularly in the context of cardiovascular and respiratory health. In addition, the article addresses the social aspect of vaping as a significant challenge faced by national public health institutions, with a special focus on the prevalence of addiction among youth. Methods: We carried out a comprehensive review using PubMed and Google Scholar, with a primary focus on literature published within five to eight years. The searches were performed using “vaping”, “e-cigarettes”, “smoking”, “COPD”, “nicotine replacement therapy” and the names of its components as search terms to retrieve relevant articles. Furthermore, references cited in the selected articles were also included in the analysis. Results: The current evidence suggests that while e-cigarettes may pose a lower risk than traditional cigarettes, they are not risk-free. Dual use of cigarettes and e-cigarettes increases cardiovascular risk and is comparable to the risks associated with exclusive cigarette smoking. Studies suggest that long-term e-cigarette use may result in increased aortic stiffness, elevated heart rate, heightened risk of atherosclerosis and diminished lung function, increased airway resistance, especially in individuals with pre-existing conditions like asthma. Exposure to aerosolized chemicals present in e-liquids poses risks of chronic respiratory diseases. Conclusions: The precise impact of e-cigarette use on health needs further research and long-term observations. Particular concern arises from the unregulated composition of e-liquids, which are gaining popularity among youth, thereby promoting early nicotine addiction and normalizing the use of tobacco products. Efforts to regulate the composition of e-liquids and the use of harmful additives are crucial to mitigate the potential health risks associated with vaping.